INCLUSIVE PARADIGM âRELIGION PLURALISM ON AL-QURAN PERSPECTIVE (QS. al-Baqarah/2: 136-137 & QS. Ali Imran/3: 64 Analysis) - Maulasa, Aisma; Rahman, M. Gazali (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
This writing is discussing Alquran perspective about the attitude which should be owned by every Moslem in facing religion pluralism as something is possible and factual. By doing deep analysis on QS AlBaqarah /2: 136-137 and QS Ali Imran /3: 64, it is clear that pluralism is factual and be sunnatulah which should be exclaimed its truth. The three verses are also claim five ideal forms which should be had and implemented by all Moslem in regulating their interaction with other religion followers. As the biggest inspiration of a Moslem, then the finding meaning on Alquran verses will minimalize even erupt all exclusive paradigm on religion which for long time constraint the harmony of religion relationship. Exclusive religion bears, because there is misunderstanding and less of understanding about Alquran verses.Â ———-Tulisan ini menyorot pandangan Alquran tentang sikap yang seharusnya dimiliki oleh setiap muslim dalam menyikapi pluralitas agama sebagai sesuatu yang niscaya dan faktual. Melalui analisis mendalam terhadap QS. al-Baqarah/2: 136-137 dan QS. Ali Imran/3: 64, tampak jelas fakta pluralitas sebagai sunnatullah yang harus diakui keberadaannya. Ketiga ayat tersebut juga menegaskan lima bentuk sikap ideal yang harus dimiliki dan diimplementasikan oleh setiap muslim dalam menata interaksinya dengan penganut agama lain. Sebagai sumber inspirasi terbesar seorang muslim, maka penyingkapan makna di balik ayat-ayat Alquran tersebut akan meminimalisir bahkan mengikis habis sikap ekslusivis beragama yang selama ini telah memasung keharmonisan hubungan antaumat beragama, sebab lahirnya sikap ekslusivis beragama tidak terlepas dari adanya miss understanding dan kedangkalan pemahaman terhadap ayat-ayat Alquran.